Multiculturalism in the Design Work of Indonesian Women Designers - Agustin, Senja Aprela; Saidi, Acep Iwan; Damajanti, Irma (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Multiculturalism has become a prominent issue in media communication, serving as both a communication strategy and a form of awareness for creators, particularly in visual communication design media. Most of the previous findings on the study of multiculturalism in the media suggest that different cultural backgrounds must be considered for global brands to reach diverse markets since visual language is not universal. In addition, other studies explore the interpretation of multiculturalism ideas in the media and practice participatory design research to communicate multiculturalism value through visual communication media. Nevertheless, in Indonesia, the interpretation study of multiculturalism in designs, especially those created by women designers, as a manifestation of multiculturalism awareness seems to be underexplored. To narrow the gap, this study uses the visual semiotic theory of Roland Barthes to investigate the multicultural significance represented in visual images in the work of Indonesian women designers by outlining the levels of denotative and connotative meanings which develop into myth. This research reveals that the idea of multiculturalism in the design work of Nita Darsono and Sanchia Hamidjaja can provide other counter-knowledge in representing the diversity amongst the hegemony of a single and standardized body myth, such as white skin, ideal body, and race, in media. This approach better understands the audiences and appreciates cultural diversity. Overall, this study sheds light on the importance of multiculturalism in visual communication design media, particularly in representing diversity and challenging hegemonic norms. It highlights the need for more research in this area, particularly from underrepresented perspectives, such as women designers in Indonesia.